The Fourth Industrial Revolution - Challenges to Entrepreneurship and Business Management - Radev, Kiril (Research Papers, 2018)
The report presents a part of the results of a complex author’s research study with the main purpose of defining the main aspects of future changes in socio-economic relations as a result of the ubiquitous introduction of smart technologies in context with the goals of Industry 4.0. The survey is intended for academics, executives and experts from the public sector and business. It is accomplished with the help of a specially developed author’s methodology, including a large number of analytical and prognostic scientific methods. Used are process approach and systematic approach. The results of the study outline the directions and areas for adaptation of modern paradigms and models for public sector management, entrepreneurship and business, within the framework of the fourth Industrial Revolution - Industry 4.0.